Representations of Childhood in the Novel Papi by Rita Indiana Hernández (Palimpsesto, 2024)
In this paper, the novel Papi by Rita Indiana Hernández (2005) is analyzed, paying particular attention to the representation of childhood as both a reproduction and a challenge to Western discourses that conceive the child not as an entity in itself, but as a “being in the making” (Castañeda, 2002). The analysis examines how Hernández takes advantage of literary discourse and intermedial language to question political and social constructions of childhood. It concludes that, by the end of the novel, the girl becomes an agent of transformative change (Castañeda, 2002), highlighting her care for her sick mother as ethical and affective labor that contrasts with the consumption dynamics and market logic that governed the spectacularized relationship (Duchesne-Winter, 2008) with her father.
Keywords: Rita Indiana Hernández; Dominican Literature; Representations of Childhood